ESKATOLOGI MASA DEPAN DAN ETIKA KEMARTIRAN DIDALAM YOHANES 16:1-2 - Tarigan, Yohanes (Jurnal Amanat Agung, 2022)
Abstracts: Eschatology and ethics in the Gospel of John are topics that have captured the attention of scholars, as they pertain to the existence of future eschatology and ethics within the Gospel of John, which will be the focus of this paper. The study of the relationship between eschatology and ethics in the New Testament is not new in biblical studies; many scholars have discussed it, but they typically do so in relation to the Synoptic Gospels or the writings of Paul, rather than the Gospel of John. Therefore, the study of the relationship between future eschatology and ethics in the Gospel of John is something significant. However, its significance is not only viewed in terms of novelty but also in terms of its relevance to the lives of believers as they live out their faith in this world. Through research employing an exegetical method focused on John 16:1-2, the presence of future eschatology in the form of impending death and persecution, as well as the ethics of martyrdom, was discovered. Additionally, a relationship between future eschatology and the ethics of martyrdom was found, in which one aspect of this relationship is that the ethics of martyrdom serves as a means of transformation, turning what is typically considered a negative and meaningless act, such as death, into something positive and meaningful. Keywords: Future eschatology, ethics of martyrdom, death, impending persecution. Abstrak: Eskatologi dan etika dalam Injil Yohanes adalah topik yang cukup menarik perhatian para ahli, terkait keberadaan eskatologi masa depan dan etika di dalam Injil Yohanes yang akan menjadi penelitian dalam tulisan ini. Studi tentang relasi eskatologi dan etika dalam Perjanjian Baru bukanlah hal yang baru dalam studi biblika, banyak para ahli yang sudah membicarakannya, tetapi para ahli biasanya membahasnya dari Injil Sinoptik atau tulisan Paulus tetapi tidak dari Injil Yohanes. Oleh karena itu studi relasi eskatologi masa depan dan etika dalam Injil Yohanes adalah sesuatu yang signifikan,namun demikian signifikansinya bukan saja ditinjau dari masalah kebaruan, tetapi juga bagi kehidupan orang percaya dalam menjalani imannya di dunia ini. Melalui penelitian yang menggunakan metode eksegesis yang berfokus pada teks Yohanes 16:1-2 ditemukan keberadaan eskatologi masa depan berupa kematian dan penganiayaan yang akan datang dan juga etika kemartiran. Selain itu ditemukan juga adanya relasi eskatologi masa depan dan etika kemartiran yang mana salah satu bentuk relasinya etika kemartiran memiliki peran sebagai sarana transformasi yang mentransformasi kematian yang biasanya dianggap buruk menjadi sebuah tindakan yang positif dan berarti. Kata-kata kunci: Eskatologi masa depan, etika kemartiran, Yohanes 16:1-2, kematian, penganiayaan yang akan datang